Breast cancer stem cells: new therapeutic approaches. (November 2012) - Ferrari, Paola; Nicolini, Andrea
SUMMARY  Breast cancer stem cells are defined as a small subset of cells within a cancer that constitutes a reservoir of self-sustaining cells; they are low-dividing, have a reduced ability to undergo apoptosis and a higher ability of DNA repair, making them more resistant to conventional radiation and chemotherapy. The recent better understanding of the mechanisms of resistance to therapy related to stem cells has opened new scenarios and perspectives for therapeutic approaches. Some drugs active against breast cancer stem cells have been used in cancer therapy for years, other approaches are currently under clinical trials and many drugs are still in a preclinical phase. Only controlled clinical trials will answer the question whether or not these new therapeutical approaches alone or combined with the ongoing treatments significantly improve the outcome of breast cancer patients.